Clinical, histopathological and immunohistochemical characterization of a novel equine ocular disorder: heterochromic iridocyclitis with secondary keratitis in adult horses. (17th November 2014) - Pinto, Nelson I.; McMullen, Richard J.; Linder, Keith E.; Cullen, John M.; Gilger, Brian C.
Abstract Objective To describe the clinical, histopathologic and immunohistochemical characteristics of an equine ocular inflammatory disease resulting in anterior uveitis and corneal endothelial inflammation associated with iris pigment dispersion and retrocorneal fibrous membrane (RFM) formation. Design Retrospective study. Animals studied Sixteen horses with evidence of pigmented keratic precipitates (KPs), corneal edema, and/or iris depigmentation. Information collected from the medical records included signalment, clinical signs, prereferral treatment duration and response to therapy, ophthalmic examination findings, postreferral treatment, response to therapy, and outcome. Results Twenty‐one eyes from 16 horses were affected. Age ranged between 9 and 25 years (Average 16.1 years). Blepharospasm, epiphora, and/or corneal opacification were the first clinical signs noted. At the time of referral pigmented KPs, corneal edema, iridal depigmentation, and retrocorneal membranes were commonly seen. Treatment included topical and/or systemic anti‐inflammatories and antibiotics with variable response. Reduction or cessation of anti‐inflammatory therapy resulted in worsening of clinical signs and disease progression. Eight eyes ultimately required enucleation. Histopathology changes include iridal pigment loss and dispersion, RFM formation, and keratitis. Variable degrees of lymphoplasmacytic inflammation were dominated by T‐cells within the corneal stroma, RFM, iris, and ciliary body with occasional multinucleated giant cells. Conclusions Heterochromic iridocyclitis with secondary keratitis (HIK) is characterized by uveal inflammation with pigment dispersion and suspected corneal endothelial dysfunction. Horses being treated for HIK require diligent and frequent follow‐up examinations in combination with aggressive local immune suppression to control the disease. However, HIK may not respond to therapy and enucleation may ultimately be required to ensure the horse's comfort.